Entrepreneurship and Economics of Pesantrens in Lombok Island - Muhammad Salahuddin Malik; Nurhilaliati Nurhilaliati; Zaenal Arifin Munir (Shirkah: Journal of Economics and Business, 2019)
Religion is often alleged for being a barrier to development. Pesantren, as one of the instruments of religious empowerment, has occasionally even become subjects juxtaposed with religious failures. In contrast, pesantren has never been modest and consistently responded to every detail of changes. This is where the innovative and creative behavior of pesantren communities is examined. This study aims to analyze such pesantrens in Lombok island to improve innovation and creativity to enter the economic and business domain. This study enriches the discourse of economic communities in the pesantren for which some have been structured and others are still looking for ideal patterns for the economic changes that occur in society. Keywords: social change, paradigm, pesantren, entrepreneurship